(untitled) (Materiali di Estetica. Terza serie, 2017)
The recent philosophical debate about the musical ontology, between Platonist and Nominalist positions, has to face several unsurmountable objections. The aesthetics of Roman Ingarden, in spite of intrinsic limitations, can be considered in order to relaunch the research about the ontological status of musical works. Three Ingarden’s ideas seem particularly useful: the work of music as pure intentional object, as scheme with many points of indeterminacy and as object founded on score, performance or recording. A comparison arises with the theory of documentality proposed by Maurizio Ferraris.